Olympic Academy Establishment in Oman: Hindrances & Enablers - Al Adwani, Hisham Salim (Πανεπιστήμιο Πελοποννήσου, 2013)
Oman is located in southwest Asia on the southeast coast of the Arabian Peninsula. It is an IOC member since 1982 and participates in the Olympic Games since 1984. However, despite the fact that Oman is an active member of the Olympic Movement there is no Olympic Academy in the country to promote Olympism. The main aim of this study is to investigate the hindrances and the enablers existing in the process of establishing the Oman Olympic Academy. The methodology that employed is qualitative (interviews with sports specialists from different categories who have experience in sport and Olympics in the country for many years). The results of this study were: a) reflected the current thoughts in Oman regarding the establishment of an Olympic Academy, b) allowed comparison with Olympic Academies functioning in the Asia continent, c) leaded to greater understanding of the challenges the establishment of the National Olympic Academy in Oman faces and d) leaded to suggestions towards establishing an Olympic Academy in Oman.
Keywords: Olympics; Ολυμπιακοί αγώνες; Physical education and training - Oman; Φυσική αγωγή και εκπαίδευση - Ομάν; Olympic Academy; Oman; Ολυμπιακή Ακαδημία; Ομάν